2017
DOI: 10.1016/j.scitotenv.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-conditioned rocky coast systems: A case study from Wilczekodden, Svalbard

Abstract: This paper presents the results of an investigation into the processes controlling development of a cryo-conditioned rock coast system in Hornsund, Svalbard. A suite of nested geomorphological and geophysical methods have been applied to characterise the functioning of rock cliffs and shore platforms influenced by lithological control and geomorphic processes driven by polar coast environments. Electrical resistivity tomography (ERT) surveys have been used to investigate permafrost control on rock coast dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…In general, over the last decade, Svalbard coastal studies have been concentrated on the coastal zone response to shifts in sediment supply associated with changes in local ice masses and paraglaciation (e.g., Bourriquen et al, ; Mercier & Laffly, ; Sessford, Strzelecki, & Hormes, ; Strzelecki et al, ; Zagórski, ); ephemeric pulses of sediments from snow‐fed streams (Lønne & Nemec, ; Strzelecki, Long, & Lloyd, ); or the controls of coastal permafrost development (Kasprzak et al, ). Recent years had also brought some advances in local rocky coast systems that dominate over coastal landscape in numerous Svalbard fjords (e.g., Kasprzak et al, ; Strzelecki, ; Strzelecki, ; Strzelecki et al, ; Świrad, Migoń, & Strzelecki, ). Most recently, Jaskólski, Pawłowski, and Strzelecki () reported on the impact of geohazards including coastal changes on the state of abandoned Arctic town—Pyramiden in Northern Billefjorden.…”
Section: Introductionmentioning
confidence: 99%
“…In general, over the last decade, Svalbard coastal studies have been concentrated on the coastal zone response to shifts in sediment supply associated with changes in local ice masses and paraglaciation (e.g., Bourriquen et al, ; Mercier & Laffly, ; Sessford, Strzelecki, & Hormes, ; Strzelecki et al, ; Zagórski, ); ephemeric pulses of sediments from snow‐fed streams (Lønne & Nemec, ; Strzelecki, Long, & Lloyd, ); or the controls of coastal permafrost development (Kasprzak et al, ). Recent years had also brought some advances in local rocky coast systems that dominate over coastal landscape in numerous Svalbard fjords (e.g., Kasprzak et al, ; Strzelecki, ; Strzelecki, ; Strzelecki et al, ; Świrad, Migoń, & Strzelecki, ). Most recently, Jaskólski, Pawłowski, and Strzelecki () reported on the impact of geohazards including coastal changes on the state of abandoned Arctic town—Pyramiden in Northern Billefjorden.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Svalbard shore, the influence of the saline and relatively warm sea water on the permafrost in the land zone has not been, until recently, given adequate attention, and the existing schemes of groundwater circulation have not concentrated on the coastal zone [98,99]. The phenomenon of sea water intrusion inland has been illustrated in the Hornsund region with the use of electrical resistivity tomography [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Recent thermal measurements of the near-surface ground parts performed in the vicinity of the study area indicate that in the summer, the tundra-covered land surface may reach temperatures above 20 • C [77], and the temperature of the ground at the depth of 1.5 m may reach up to 4.3 • C in August [27]. Based on geophysical imaging, a conclusion may also be drawn that the permafrost base in the coastal zone is additionally influenced by the thermal currents and salination of the seawater [6,7].…”
Section: Study Areamentioning
confidence: 91%
See 1 more Smart Citation
“…7). Indeed studies in the High Arctic have shown how periglacial processes and especially the interaction of permafrost, variable lithology, weathering and slope processes controls cliff evolution with wave action rejuvenating the system during high sea level stands producing high rates of cliff retreat (Strzelecki et al, 2017). Ostracods suggest the presence of brackish pools, so it is likely that these loams were deposited adjacent to a high sea level and, stratigraphically, should date to the last cold stage (Devensian).…”
Section: Discussion: Sea-levels Periglaciation and Long-term Coastalmentioning
confidence: 99%